Need for Intelligent Software Cost Estimation and its Methods: A Comprehensive Overview - Rekha, M. S.; Malakreddy A., Bharathi (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Software cost estimation stands as a critical phase in the software development life cycle, impacting budgeting, resource allocation, and project planning. The dynamic and complex nature of software projects, along with the rapid evolution of technology, necessitates an intelligent approach to cost estimation. This paper presents a comprehensive overview of the need for intelligent software cost estimation and delves into various methods employed to achieve accuracy and efficiency in estimations. It examines traditional models, such as COCOMO and Function Point Analysis, alongside modern techniques that leverage machine learning and artificial intelligence to adapt to the complexities of software projects. By comparing the effectiveness, challenges, and applicability of each method, the paper highlights the evolution of cost estimation practices and the growing importance of incorporating intelligence into these processes. It concludes with insights into future directions, emphasizing the integration of predictive analytics and data-driven decision-making in improving the reliability and precision of software cost estimations. Through this overview, the paper aims to provide stakeholders with a deeper understanding of intelligent cost estimation methods, facilitating better planning and management of software projects.